Lappiske eventyr og folkesagn - Qvigstad, J. (Just), b. 1853.; Sandberg, G.; Moe, Moltke, 1859-1913. (Kristiania, A. Cammermeyer, 1887)
With added illustrated title-page, also. Mode of access: Internet.